Evaluation of medication dose adjustments in patients with impaired renal function using different online drug information databases - OKUYAN, BETÜL (BMJ Publishing Group, 2020)
Objectives: Clinical pharmacist-led medication dose adjustment is required to provide safe and effective pharmacotherapy in patients with impaired renal function. This study aimed to assess clinical pharmacist-led medication dose adjustments in hospitalised patients with impaired renal function by comparing three online drug information databases. Methods: This retrospective observational study was conducted in an internal medicine ward between November 2016 and February 2017 among hospitalised patients with at least one estimated glomerular filtration rate (eGFR) value <60 mL/min/1.73 m2. Clinical pharmacist-led medication dose adjustments according to eGFR were performed by comparing three online drug information databases: Micromedex, Medscape and Lexicomp. The number of items related to dose adjustments detected during the study period and the concordance between databases were evaluated. Results: This study was conducted among 100 hospitalised patients (mean age 74.6±13.2 years) with impaired renal function. Clinical pharmacists detected at least one medication dose adjustment in 71.0% of patients. Among these patients, it was found that physician-led medication dose adjustments were made in only 15.5% of them. Of 1053 medications, the number of medications that required dose adjustments were 149 (14.2%), 151 (14.3%) and 163 (15.5%) according to Micromedex, Medscape and Lexicomp, respectively. The Fleiss kappa coefficient was 0.875 and the agreement of the three clinical decision support systems were almost perfect. Conclusions: In renal dose adjustments, Micromedex, Lexicomp and Medscape are concordant as online drug information databases. Clinical pharmacists could detect medication dose adjustment requirements in hospital patients with impaired renal function. The potential positive impact of clinical pharmacist-led medication dose adjustment should be investigated in further studies. © European Association of Hospital Pharmacists 2020. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: chronic renal failure; clinical pharmacy; general medicine (see internal medicine); internal medicine; medical errors